73 PREVALENCE OF SECONDARY HYPERPARATHYROIDISM BY VITAMIN D STATUS IN OLDER IRISH ADULTS. (25th October 2022) - Fitzpatrick, D; Laird, E; Hoey, L; Hughes, C; McNulty, H; Ward, M; Strain, JJ; Tracey, F; Molloy, A; Cunningham, C; Carroll, KM
Abstract: Background: Secondary hyperparathyroidism commonly results from vitamin D deficiency and can lead to accelerated bone turnover and bone loss, especially at cortical sites like the hip. It can also attenuate the response to antiresorptive treatments used for osteoporosis. However, several factors may influence PTH response. We aimed to identify the prevalence of secondary hyperparathyroidism by categories of vitamin D status in older Irish adults attending a bone health clinic. Methods: The study population consisted of older adults (aged over 60 years) attending a bone health clinic at a large hospital. Participants with a serum calcium >2.5 mmol/l and eGFR <30 ml/min were excluded to avoid cases of primary hyperparathyroidism or elevated serum PTH due to advanced renal disease. Hyperparathyroidism was defined as a serum PTH > 65 pg/ml. 25 hydroxyvitamin D (25(OH)D) was measured with liquid chromatography mass spectroscopy. Results: There were 800 cases identified, mean age 72.9 +/- 7.9 years, and 85.3% were female. The prevalence of secondary hyperparathyroidism by 25(OH)D categories were 28.1% (<30nmol/l), 17.4% (30-49.9 nmol/l) and 8.0% (50-74 nmol/l). Older age (P < 0.03) and lower eGFR (P = 0.01) were associated with hyperparathyroidism independent of vitamin D status. Conclusion: Nearly one-third of patients who were vitamin D deficient (<30 nmol/L) and one-sixth who were insufficient (30-49.9 nmol/l) had hyperparathyroidism, similar to the results of other studies. However, hyperparathyroidism was also observed in 8% of those with 25(OH)D levels between 50 -74 nmol/l, suggesting that higher levels i.e. ≥ 75 nmol/l may be preferable in older adults. Lower eGFR and older age were also independently associated with higher PTH, consistent with previous research. Higher dietary and supplemental calcium intake is also known to suppress PTH response, though we were not able to account for this in our study.